A novel titania/graphene composite applied in reinforcing microstructural and mechanical properties of alkali-activated slag. (September 2021) - Ren, Jie; Guo, Si-Yao; Qiao, Xiao-Li; Zhao, Tie-Jun; Zhang, Li-Hai; Chen, Ji-Chou; Wang, Qiaorui
Abstract: Alkali-activated slag (AAS) binder with low carbon footprint is a promising alternative to high energy-embodied ordinary Portland cement binders. However, wider applications are hindered by their ceramic-type fractural behaviours. This study involves improving the microstructure and mechanical properties of alkali-activated slag pastes by using an in-situ fabricated titania/graphene composite assisted with a novel titania intercalating method. The result indicates that titania located in between the layers of graphene could make graphene homogeneously dispersed in an aqueous solution, which is conducive to obtaining well-dispersed graphene nanoparticles in AAS pastes. Besides, the highly dispersed titania/graphene composites lead to a less disordered microstructure of AAS paste compared to the normal counterpart. Moreover, both the compressive strength, flexural strength, Young's modulus were improved as the content of titania/graphene composites (0%-0.03 wt%) increased. In addition, the fractural behaviours were also improved remarkably evidenced by a 89.7% increase of flexural toughness for AAS pastes with 0.03% titania/graphene composite. Scanning electron microscopy observations confirmed that the microstructure of the AAS pastes with titania/graphene composites was denser compared to normal AAS which is probably due to the effects of crack bridging and branching. Overall, the developed new intercalating method could be used to improve the dispersibility of graphene which is then employed effectively for reinforcing microstructure and mechanical properties of AAS binders. Highlights: An improved dispersibility of graphene platelets was achieved by intercalating titania nanoparticles. Titania/graphene composite was for the first time employed for enhancing alkali-activated slag pastes. Titania/graphene reinforced alkali-activated slag pastes display fewer cracks and improved mechanical properties. Low cost and simple in-situ method of titania/graphene synthesis provides AAS with more practical applications.